2009
DOI: 10.1677/erc-08-0175
|View full text |Cite
|
Sign up to set email alerts
|

Novel mechanism of IGF-binding protein-3 action on prostate cancer cells: inhibition of proliferation, adhesion, and motility

Abstract: IGF-binding protein-3 (IGFBP-3) is a modulator of the IGF-signaling pathway and was described as an anti-cancer agent in prostate cancer. The molecular mechanisms underlying these effects remained, however, largely undefined. We analyzed the influence of recombinant IGFBP-3 on cell proliferation of PC3, Du145, and LNCaP prostate cancer cells. As expected, IGFBP-3 inhibited IGF-stimulated cell proliferation by blocking IGF-mediated proliferation signals, but we observed an IGF-independent inhibitory effect of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 58 publications
1
31
1
1
Order By: Relevance
“…59 On the contrary, some studies have shown IGFBP-3 significantly reduces the migration of PC3 prostate cancer cells, Ewing's sarcoma cells, and non-small cell lung cancers, further emphasizing the multifunctional roles of IGFBP-3 in different human cancers. 4,35,38 Our results demonstrating IGFBP-3's involvement in GBM tumor cell invasion in vitro are also consistent with the findings of previous studies on malignant melanoma and esophageal squamous cell carcinoma.…”
Section: Discussionsupporting
confidence: 92%
“…59 On the contrary, some studies have shown IGFBP-3 significantly reduces the migration of PC3 prostate cancer cells, Ewing's sarcoma cells, and non-small cell lung cancers, further emphasizing the multifunctional roles of IGFBP-3 in different human cancers. 4,35,38 Our results demonstrating IGFBP-3's involvement in GBM tumor cell invasion in vitro are also consistent with the findings of previous studies on malignant melanoma and esophageal squamous cell carcinoma.…”
Section: Discussionsupporting
confidence: 92%
“…Brief ly, IGFbP3 has been shown to inhibit proliferation, adhesion, migration, and invasion processes of prostate tumor cells (24). Studies that investigated cd40 expression in tissues from patients with prostate cancer have concluded that invasive prostate cancer is a cd40-negative tumor (25).…”
Section: Discussionmentioning
confidence: 99%
“…Among the genes affected by Ets-1 in Pc3 cells and involved in apoptosis, we analyzed AR, IGFbP3, VAV3, PTH, PRKCE, IFI16, CCL2, DLC1, XAF1 and TLR4 which are known to be involved in prostate cancer (20,24,(28)(29)(30)(31)(32)(33)(34)(35) (Tables III and IV). AR, IFI16, CCL2, DLC1, XAF1 and TLR4 were found to be more than 10-fold down-regulated in Ets-1 blocked Pc3 cells compared to mock control cells, whereas IGFbP3, VAV3, PRkcE, and PTh were shown to be more than a 10-fold up-regulated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[45][46][47] Furthermore IGFBP3 was described to inhibit cellular adhesion, migration and invasion, as well as enhance the efficacy of radiation-, chemotherapeutic-and pro-apoptotic agents. 47,48 The results of the in vitro studies were partially reproduced in vivo, where recombinant IGFBP3 reduced tumor size and inhibited vascularization in mouse tumor models. [49][50][51] Although repeatedly proposed, currently no clinical studies investigating the antitumor activity of IGFBPs are registered at the database of clinical trials.…”
Section: Igf Binding Proteins (Igfbps) As New Therapeutic Approachmentioning
confidence: 99%